Removal of Selected Micropollutants by Ozonation - J. Derco; J. Dudáš; K. Šilhárová; M. Valicková; M. Melicher; A. Luptáková (Chemical Engineering Transactions, 2012)
Micropollutants are natural and manmade substances, such as pharmaceutical and personal care products, pesticides and industrial chemicals, which have been detected in water and in the environment in very low concentrations. Many of them, raise considerable toxicological concerns, are poorly removable by conventional wastewater treatment technologies. To reduce the release of such substances into the aquatic environment two advanced treatment processes based on ozone utilisation were investigated in laboratory scale. Degradation of two types of micropollutants, i.e. selected organochlorine pesticides and oil compounds have been studied. The results of ozonation and O3/(UV show that the highest removal rates were observed during the first 5 minutes of ozonation for all investigated pollutants. Removal efficiencies of chlorinated pesticides were in the range from 70.2 to 90.7 % after 60 minutes of ozonation. Removal efficiencies of about 90 % were observed for all investigated BTX compounds after 40 minutes of ozonation..